THE EFFECT OF PHYTASE ENZYME ON APPARENT DIGESTIBILITY OF FOUR VEGETATIVE FOOD IN RAINBOW TROUT (ONCORHYNCHUS MYKISS) - M. Rahmati; A. Abedian; R. Nazari (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2006)
We investigated the effect of Phytase enzyme on phosphorus, protein, fat, dry matter and Energy digestibility of four vegetative food comprised of wheat meal (WM), corn meal (CM), wheat bran (WB), rice bran (RB) in rainbow trout feeding. A base diet including fish, soybean and meat flour, was prepared. Four diets were prepared using a mixture of 75% base diet and 25% WM or CM and 85% base diet and 15% WB or RB with similar gross energies. Chromic oxide was added as 0.5% of the diet and used as an indigestibility marker. A phytase solution was sprayed on all diets at a minimum concentration of 1000 phytase units per Kg (FTU/Kg) of dry diets. Experiments were carried out in two cubic meter tanks that were filled with 500 liters of water. Maximum and minimum of temperature, oxygen and pH were 18 and 15°C;8 and 6.8mg/l and 7.7 and 7.5 respectively. Results showed no significant effect of Phytase on the amount of bone phosphorus and protein digestibility (P>0.05), while there was an increase in these indexes with Phytase supplementation. Moreover, Phytase significantly improved digestibility of dry matter. Results also showed that kind of diets had different effects on the nutritional digestibility. The diet containing of WM was the best with those containing CM, WB and RB gradually losing their suitability in terms of the nutritional digestibility. Due to their availability and suitability, we suggest that these diets, especially that containing WM be used in Rain bow trout culture.